Do Diversity Reputation Signals Increase Share Value?. (21st November 2014) - Cook, Alison; Glass, Christy
<x xml:space="preserve">Abstract</x> This analysis contributes to the ongoing scholarly debate regarding the relationship between firms' efforts to promote diversity and financial performance. Most research contributing to this debate focuses on specific efforts of firms, such as progressive human resource policies and leadership personnel changes, on firm‐level outcomes. Much less research focuses on the impact of reputational signals on performance. However, we argue that reputation signals may provide an even stronger test of the impact of diversity efforts on performance. We analyze the impact of diversity awards, which recognize companies at the forefront of progressive human resource policies, on share value. We use event study methodology to test hypotheses derived from signaling theory to predict investors' reaction to the announcement of diversity awards. Overall, we find that diversity award recipients are rewarded for these efforts by a significant increase in share price. Our research lends support to the business case for diversity by demonstrating that investors interpret diversity reputation signals as contributing to firms' financial value. Further implications of these findings for corporate decision makers, policy makers, and scholars are discussed.